A study on properties of wax (palm oil based) for industrial uses on machining application / Muhamad Azli Alias and Badaruddin Abdul Wahab - Alias, Muhamad Azli; Abdul Wahab, Badaruddin (1996)
Machining is a mechanical process where excess material from a workpiece can be removed by cutting action to produce a part of specified geometrical shape and surface finish. Machining can be performed on virtually all solid materials even though the term commonly applies to the cutting of metals, alloys, plastics and woods. In this paper, we will discuss whether there is a possibility to use the palm oil based wax for machining application. At the moment, different ferrous and non-ferrous materials are used for practical training purposes by different educational and training organisation. However, the price of such material is very expensive. As for prototype making with use of high-technology machines, such as CNC machine, require cheaper and reliable material to balance the cost of its operations. Hence an attempt is made to substitute these materials by the "palm oil based wax produced in Malaysia. This project gives the approaches taken in this direction.